(untitled) (Journal of Partial Differential Equations, 2025)
In this paper, we consider the Cauchy problem of d-dimensional (d=2,3) tropical climate model without thermal diffusion and construct global smooth solutions by choosing a class of special initial data (u_0,v_0,θ_0) whose L^2 norm can be arbitrarily large, and improve the previous results in [1,2].